Analysis of factors influencing the use of accounting information on SMEs in Badung Regency - Rai Gina Artaningrum; Kadek Nita Sumiari; Ni Nengah Lasmini (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
This study aims to analyze the level of education, business scale, accounting training, accounting knowledge, and the use of accounting information in micro, small, and medium enterprises in the Badung district. This research is quantitative in nature, and the data used consists of primary data obtained by distributing questionnaires to MSME actors in the Badung regency. The population of this study comprises all MSMEs registered in the Badung Regency who have paid their annual taxes, amounting to 3,350 MSMEs. The sample for this study was selected through simple random sampling, utilizing the Slovin formula. The results revealed that the level of education, accounting training, and accounting knowledge had a positive effect on the use of accounting information in micro, small, and medium enterprises in the Badung district. However, business scale exhibited a negative effect on the use of accounting information in micro, small, and medium enterprises in the Badung district.